Evaluation of the BICGSTAB(l) algorithm for the finite-element - Topsakal, Erdem
We discuss the application of non-stationary Krylov-subspace-based iterative solvers to linear systems resulting from the application of the finite-element/boundary-integral method. A fairly new conjugate-gradient-based solver, BICGSTAB(l) is further described. The performance of several solvers is tested on a linearly tapered slot antenna (LTSA). Results showing the convergence characteristics and memory requirements are also given.
Keywords: Matrix decomposition; Matrix inversion; Iterative methods; Finite element methods; FDTD methods; Boundary integral equations; Iterative matrix solvers; Finite element boundary integral method